PERILAKU PASIEN ABORTUS DENGAN KEJADIAN ABORSI DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Kiki Megasari (Menara Ilmu, 2019)
Abortion is a health problem caused by people's behavior that tends to assume thatabortion is the best way to deal with unwanted pregnancies. Data obtained on the numberof abortion cases in Indonesia and the number of complications Abortus in Riau Provincecontinues to increase every year. This study aims to determine the relationship betweenknowledge, attitudes and actions abortus patients on the incidence of abortion in RSUDArifinAchmad Riau Province. This research is a type of Analytic-Quantitative researchwith Corelation Study design with Total Sampling technique. The data was collected bydistributing questionnaires to Abortus patients treated in RSUD ArifinAchmad RiauProvince amounting to 32 people. The results of this research is the knowledge level ofrespondents 62.5% Less, Response Attitude 56.2% Negative, Action respondents 53.1%tend to accept Abortion behavior. There is a significant relationship between knowledge,attitudes and actions on Abortion events with p = 0,000 <0,05. Value (r) knowledge ofAbortion Incidence 0.703, KD 49.4. The value of (r) attitudes toward the incidence ofAbortion 0.851, KD 72.4. The value (r) of action against the occurrence of Abortion 0.840,KD 70.5. The conclusion of this research is that Attitudes have a very strong effect onAbortion occurrence that is equal to 74,2% (r = 0,851). It is expected that health workerscan provide information and counseling to pregnant women about the dangers of abortion.Keywords: Abortion Patient Behavior, Abortion Occurrence